Period change rates of Large Magellanic Cloud Cepheids using mesa. Issue 1 (26th September 2022) - Espinoza-Arancibia, F; Catelan, M; Hajdu, G; Rodríguez-Segovia, N; Boggiano, G; Joachimi, K; Muñoz-López, C; Ordenes-Huanca, C; Orquera-Rojas, C; Torres, P; Valenzuela-Navarro, Á
ABSTRACT: Pulsating stars, such as Cepheids and RR Lyrae, offer us a window to measure and study changes due to stellar evolution. In this work, we study the former by calculating a set of evolutionary tracks of stars with an initial mass of 4 to 7 M⊙, varying the initial rotation rate and metallicity, using the stellar evolution code modules for experiments in stellar astrophysics (mesa ). Using Radial Stellar Pulsations (rsp ), a recently added functionality of mesa, we obtained theoretical instability strip (IS) edges and linear periods for the radial fundamental mode. Period–age, period–age–temperature, period–luminosity, and period–luminosity–temperature relationships were derived for three rotation rates and metallicities, showing a dependence on crossing number, position in the IS, rotation, and metallicity. We calculated period change rates (PCRs) based on the linear periods from rsp . We compared our models with literature results using the geneva code, and found large differences, as expected due to the different implementations of rotation between codes. In addition, we compared our theoretical PCRs with those measured in our recent work for Large Magellanic Cloud Cepheids. We found good overall agreement, even though our models do not reach the short-period regime exhibited by the empirical data. Implementations of physical processes not yet included in our models, such as pulsation-driven mass-loss, an improved treatment of convection that may lead to a better description of the IS edges, as well as consideration of a wider initial mass range, could all help improve the agreement with the observed PCRs.